TIPOLOGI RUANG TERBUKA HIJAU PADA KAWASAN HUNIAN SPONTAN DI TEPI JALUR LINIER DALAM PERKOTAAN YOGYAKARTA Tinjauan Dari Morfologi Kawasan Urban Ke Rural - , Yulita Kusuma Sari; , Dr. Ir. Budi Prayitno, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Until recently, Green Open Space is considered as the most appropriate answer to the issue of ecological environment. Minimun criteria set by the goverment widened the reference inthe administration of urban green open space. However, we often forget that the ideal of green open space is the one that blends with spatial pattern character of cities and regions to consider aspects of authenticity, connectivity between spaces, and the ability to answer the challenges of ecological sustainability of the environment. Meanwhile, the city of Yogyakarta, which is triggered by various factors, coupled with the natural factors causing a unique variety of spatial patterns. History records that give rise to the diversity of human activities are at the beginning of the Yogyakarta Kingdom, then the Dutch and British occupation, the impact of the industrial revolution, political instability, the rise of the university, and modern day life as it is today. This study was to answer the challenge of Yogyakarta to provide green open spaces such as the criteria. Studies of a typology of green open space in relation to the concept of urban-rural, and the diversity of vegetation types is the first step to identify the spatial pattern of green open space at this time, in accordance with the authenticity of which is formed from the morphology of the city. The findings of this study is expected to be a reference concept in the planning of urban green open space area of Yogyakarta.